2003
DOI: 10.1034/j.1600-0625.12.s2.5.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of heparin‐binding EGF‐like growth factor (HB‐EGF) mRNA in normal human keratinocytes induced by a variety of natural and synthetic retinoids

Abstract: It was recently revealed that epidermal growth following topical treatment with all-trans retinoic acid (atRA) was at least partly induced by heparin-binding epidermal growth factor-like growth factor (HB-EGF) released from suprabasal keratinocytes. Since proliferation of keratinocytes appears to be one of the critical roles of atRA in depigmentation treatment and promotion of wound healing, HB-EGF is considered suitable for assessing the therapeutic value of topical retinoids. In this study, HB-EGF mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…In bleaching treatment with tretinoin and hydroquinone, we believe that the role of tretinoin is to wash melanin granules out of epidermis, whereas that of hydroquinone is to suppress strongly new melanin production 11,12 . Tretinoin induces exfoliation, and thus, it appears to also act as a penetration enhancer of hydroquinone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bleaching treatment with tretinoin and hydroquinone, we believe that the role of tretinoin is to wash melanin granules out of epidermis, whereas that of hydroquinone is to suppress strongly new melanin production 11,12 . Tretinoin induces exfoliation, and thus, it appears to also act as a penetration enhancer of hydroquinone.…”
Section: Discussionmentioning
confidence: 99%
“…However, because binding affinity to specific nuclear receptors (retinoic acid receptors; RARs) of ROL or RAL is far less than that of tretinoin, beneficial effects are also expected to be very moderate compared with tretinoin. Our previous study revealed that heparin‐binding epidermal growth factor‐like growth factor (HB‐EGF) mRNA, which plays a critical role in epidermal growth after retinoid treatment, 9,10 was upregulated by ROL or RAL to a similar extent as tretinoin, but only when ROL or RAL was used at 40 to 100 times higher concentration than tretinoin 11 . Because proliferation of keratinocytes and acceleration of epidermal turnover appear to be the two main mechanisms of accelerated melanin discharge by retinoids, 11,12 we consider that promotion of HB‐EGF mRNA expression may be used as an important index to evaluate the depigmenting ability of topical retinoids.…”
mentioning
confidence: 99%
“…62,63 However, the role of RARα agonists as potent modulators of gene transcription in keratinocytes is obviously not a general phenomenon, since Am580/CD336 was less effective than retinoic acid in increasing the expression of other retinoid-regulated genes in cultured keratinocytes. 64 …”
Section: Keratins Are Regulated By Ligands With Rar-specificitymentioning
confidence: 99%
“…PCR was performed using oligonucleotide primers for human ALK1 (forward primer, 5Ј-ACAA-CATCCTAGGCTTCATCGCCT-3Ј; reverse primer, 5Ј-TGGTTTGCCCTGTGTACCGAAGAT-3Ј), human ALK5 (forward primer, 5Ј-GGGGCGACGGCGTTA-CAGTGTTTCTGCCAC-3Ј; reverse primer, 5Ј-TGAGA-TGCAGACGAAGCACACTGGTCCAGC-3Ј (33) ), and human GAPDH (forward primer, 5Ј-GAAGGTGAAG-GTCGGAGTC-3Ј; reverse primer, 5Ј-GAAGATGGT-GATGGGATTTC-3Ј. (34) PCR was performed using Taq polymerase (Invitrogen) with an initial denaturation step of 5 min at 94°C, followed by 30-35 cycles of denaturation at 94°C (30 s), annealing at 55°C (45 s), and extension at 72°C (60 s). PCR products were resolved by agarose gel electrophoresis and visualized by ethidium bromide staining.…”
Section: Tgf-␤/alk1 Signaling In Chondrocytesmentioning
confidence: 99%